Use of Stratigrahpic and Structural-Facing Directions to Delineate the Geometry of Refolded Folds Near Thunder Bay, Ontario - Kehlenbeck, M. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1984)
Summary North and west of Thunder Bay Archean rocks of the western Superior province consist of metasedimentary schists, gneisses, migmatites and granitic plutonic rocks of the Quetico belt in contact with metamorphosed pillow lavas and various volcanoclastic rocks of the Wawa belt. At Hazelwood Lake steeply plunging, isoclinal folds accompanied by a pervasive east-west striking axial planar cleavageare developed in a well stratified sequence of greywackes and slates. Fold hinge lines commonly parallel the dip direction of the axial surface. Consequently, the folds close sideways and are neutral folds. In most outcrops local younging of strata is readily determined from graded beds. When bedding and local younging are projected onto the axial planar cleavage, the structural facing of the folds and the stratigraphic younging of the succession as a whole is in the direction of the younger strata along a line at right angles to the trace of bedding in the cleavage. At Hazelwood Lake the trace of bedding on the cleavage is commonly subvertical and therefore the structural facing of the folds is primarily side ways. Reversals in the structural facing direction imply that these F2 folds were generated in previously folded strata. A succession of metavolcanic rocks in contact with the polyphase deformed meta-sedimentary terrain appears also to have been folded by the F2 event. The nature of the contact prior to the F2 folding, the presence of previous folds in the metavolcanic rocks, and their stratigraphic position with respect to the grey-wackes and slates are not clear from the available data.